Board Gender Diversity And Its Impact On The Performance Of Responsible Investing Mutual Fund - Rizki Anggraeni; Cynthia Afriani Utama (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
The growth of assets under management of Responsible Investing mutual funds in Indonesia has increased rapidly, highlighting increased investor interest in non-financial factors. Despite its continuous growth, debate continues over its financial performance. Within the framework of responsible investing, the presence of women on the board is expected to contribute toward the balancing of financial and non-financial goals. However, empirical evidence related to the role of gender in investment manager governance remains scarce. This study examines panel data of 228 equity mutual funds in Indonesia over a five-year period and performs robustness checks using Propensity Score Matching. The hypotheses tested are as follows (1) whether responsible investing mutual funds outperform conventional funds during crisis and non-crisis periods; and (2) the impact of board gender diversity on responsible investing mutual fund performance. The results show that (1) responsible investing mutual funds generally underperform based on Jensen's alpha, but greater resilience during the COVID-19 crisis; and (2) gender diversity in the board of directors negatively influences performance, while positive effect is observed at the commissioner level. These findings offer insight for regulators in formulating governance policies in responsible investing mutual funds.